The Concept of Alternative Justice In The Form of Cumulative Criminal Sanctions For Corporate Crimes : Adopting The Concept of Justice of Thomas Aquinas - Eny Maryana (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2023)
: Justice according to Thomas Aquinas is the virtue of justice that involves "aliquod opus adaequantum alteri secundum aliquem aequalitatis modum", which means giving what should be received by others based on proportional equality. However, Thomas' thoughts have not been seen in the law enforcement system in Indonesia, especially in the context of corporate crime victims. Victims often do not receive justice, such as compensation and appropriate punishment for corporate criminals. Indonesia's criminal law system only recognizes two types of punishment, namely primary and additional punishments. Primary punishment includes the death penalty, imprisonment, detention, fines, and closure, with a maximum prison sentence of 20 years even if there are multiple victims with significant losses. Therefore, quantitatively speaking, this is unfair according to the principles of justice explained by Thomas Aquinas. Criminal sanctions against corporate crime perpetrators are regulated in Law Number 11 of 2020 concerning Job Creation. Although legal entities or corporations can be held accountable and punished, the primary punishment against corporations is only in the form of fines and/or additional punishments, such as confiscation of evidence, compensation, and restitution. However, the criminal sanctions in some large cases of corporate crime are not proportionate to the value of losses and the number of victims affected. Therefore, alternative thinking is needed in the context of proportionate punishment based on the principles of justice of Thomas Aquinas, namely cumulative justice. This research aims to analyze the application of cumulative law in Indonesia based on alternative justice for corporate crime victims. Alternative justice must be embodied in the form of revisions to the Criminal Code to implement a more just legal system in Indonesia. This study uses a descriptive-analytical approach with normative legal methods, and examines regulations and the Criminal Code. The results show that cumulative law as an alternative justice for corporate victims in seeking proportional justice must be applied in the legal jurisdiction of the Republic of Indonesia. This does not preclude the possibility of becoming a reality as the law advances and crime becomes increasingly sophisticated and well-organized.